(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Proper identification and quality assurance of the raw material is an essential prerequisite to ensure reproducible quality of Ayurvedic medicines. Sweta Sariva (Hemidesmus indicus), commonly known as Indian Sarsaparilla is a well-known drug and is reputed for its Dahaprasamana (alleviates burning sensations), Deepana (appetizing) and Raktashodaka (blood purifying) properties. Root is the official part of Sweta Sariva. It is very popular in Kerala as a medicine and as a health drink. Hemidesmus indicus of Periplocaceae family is considered to be the genuine source plant of Sweta Sariva, but survey of commercial samples from various states of India reveal that at present root and root-stalk of five different botanically identified plants from dissimilar families are being sold as Sariva in different parts of the country. Here a study on the anatomical and powder characters of Sweta Sariva was done so that people can easily identify the Sweta Sariva from its adulterants. The genuine Hemidesmus indicus roots are very slender with a diameter less than 1cm and they possess a characteristic pleasant smell with a sweetish taste. In the transverse section there are plenty of starch grains, prismatic crystals of calcium oxalate crystals and lactiferous ducts are seen in the cortex portion which forms the major identifying features. Three types of vessels are found in the powder microscopy.